2019
DOI: 10.3892/ol.2019.11194
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition mechanism of lung cancer cell metastasis through targeted regulation of Smad3 by miR‑15a

Abstract: Effect of targeted regulation of mothers against decapentaplegic homolog 3 (Smad3) by microRNA-15a (miR-15a) on the proliferation, invasion and metastasis of non-small cell lung cancer (NSCLC) cells and its related mechanisms were investigated. Fifty pairs of NSCLC and para-cancerous tissues were collected to identify the expression level of miR-15a in NSCLC, para-cancerous tissue, and cell lines A549, H1299, H1975 and BEAS-2B by real-time fluorescence quantitative PCR (RT-PCR); A549 cells were transfected wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…After coculture with CAFs, miR-15a-5p was also upregulated in CAFs + mimic group, the invasion and migration were decreased, E-cadherin was increased and N-cadherin was decreased, and MMP3 was reduced. Overexpression of miR-15a can signi cantly inhibit A549 cell proliferation, migration and invasion [41,42]. Collectively, overexpression of miR-15a-5p can reduce the promotion of SDF-1 secreted by CAFs on NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…After coculture with CAFs, miR-15a-5p was also upregulated in CAFs + mimic group, the invasion and migration were decreased, E-cadherin was increased and N-cadherin was decreased, and MMP3 was reduced. Overexpression of miR-15a can signi cantly inhibit A549 cell proliferation, migration and invasion [41,42]. Collectively, overexpression of miR-15a-5p can reduce the promotion of SDF-1 secreted by CAFs on NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Necroptosis was induced through lncRNA3037/miR-15a/BCL2-A20 signaling pathway [ 24 ]. miR-15a inhibits the growth and metastasis of human cancers by regulating Stat3 [ 135 ], Smad3 [ 136 ], Twist1 [ 137 , 138 ], CXCL10 [ 139 ], etc. LncRNA-107053293 miR-148a-3p LncRNA-107053293 regulated necroptosis by acting as a ceRNA of miR-148a-3p [ 25 ].…”
Section: Necroptosis and Cancer Metastasismentioning
confidence: 99%
“…The result showed that the top 20 proteins interacting with AHSG (Figure 9B ) mainly functioned in tumor suppressor, signal transduce, cancer development. 26 , 27 , 29 , 30 , 33 , 34 , 35 , 36 , 37 , 38 , 39…”
Section: Resultsmentioning
confidence: 99%